Three new species of the genus Issikiopteryx Moriuti, 1973 (Lepidoptera: Lecithoceridae: Lecithocerinae) from China - Liu, Shurong; Wang, Shuxia (Zootaxa, 2013)
The genus Issikiopteryx Moriuti is further studied in China based on the specimens collected from Zhejiang, Guizhou and Tibet. Three new species are described: I. parelongata sp. nov., I. suiyangensis sp. nov. and I. nigeriflava sp. nov. Photo-graphs of adults and genital structures are provided.